Real-World Prescription Patterns For Patients With Young-Onset Parkinson’s Disease in China: A Trend Analysis From 2014 to 2019 - Liu, Xiao-qin; Wang, Xiao-yu; Shen, Hui-ming; Pang, Wen-yuan; Zhong, Ming-kang; Ma, Chun-lai (Frontiers in Pharmacology, 2022)
Introduction Pharmacotherapy is one of the main treatments for patients with young-onset Parkinson’s disease (YOPD). Although numerous studies on the treatment of YOPD have been published, the real-world prescription patterns of these populations remain unclear in China. Methods A national comprehensive evaluation was performed to reveal the pharmacological treatment patterns in Chinese patients with Parkinson’s disease from 1 January 2014 to 31 December 2019, with patients aged 21–50 years classified as having YOPD for the subgroup analysis. Information on patients and drugs was extracted to analyse the demographic characteristics, prescription patterns, and levodopa equivalent daily dose (LED) during disease progression. Results A total of 1,134 patients with YOPD were included, and the majority were aged 41–50 years. Prescription of L-DOPA/benserazide and pramipexole accounted for more than 30 and 20%, respectively, in each year from 2014 to 2019. There was no difference in prescription patterns in terms of age, sex and geographical areas. Half of the patients with YOPD were on monotherapy, but the proportion decreased from 2016. Correspondingly, the proportion of patients receiving polytherapy increased, especially those who were prescribed more than two anti-Parkinson’s disease drugs. During the disease course, LED showed high variability, which increased over time. Conclusion L-DOPA/benserazide and pramipexole were the most frequently prescribed anti-PD drugs for patients with YOPD in China. There was a slight trend in the transition from monotherapy to polytherapy. LED increased with disease duration. Thus, we provided an overview of the prescription patterns for patients with YOPD in China.